PTU-160 Successful clearance of chronic noroviral infection by ribavirin in a patient with common variable immunodeficiency-associated enteropathy results in complete symptomatic and histopathological resolution. (28th May 2012) - Woodward, J; Ng, A; Aravinthan, A; Bandoh, B; Liu, H; Davies, S; Stevenson, P; Curran, M; Kumararatne, D
Abstract : Introduction: We have recently demonstrated an association between chronic Noroviral infection and Common Variable Immunodeficiency-associated (CVID) enteropathy. Here we describe a patient with CVID enteropathy treated with Ribavirin. Methods: A 33-year-old lady with known CVID presented to our service in 2003 with 20% weight loss, nausea and profuse diarrhoea. Investigations revealed classical appearances of CVID enteropathy with subtotal duodenal villous atrophy, but no evidence of bacterial, enteroviral or parasitic infection. Treatment with gluten withdrawal, elemental diet, and budesonide were largely ineffective and she required parenteral nutrition for malabsorption and anti-TNFα therapy with Infliximab and subsequently Humira for symptom relief. No therapy changed the degree of villous atrophy. Following 6 years of symptoms, stool was noted to be positive on PCR for Norovirus RNA. Retrospective analysis of archived duodenal biopsies revealed the presence of Noroviral RNA in all biopsies from 2003 to 2009 and RNA sequencing showed this to be the same strain of virus throughout. In view of reported in vitro activity of Ribavirin against Norovirus, this agent was commenced with therapeutic level monitoring and quantitative stool PCR for Norovirus excretion. Results: Once Ribavirin levels were >1000 ng/ml, quantitative PCR demonstrated a reduction in Noroviral excretion which then became undetectable. Simultaneously, the patient reported dramatic symptomatic relief with a change from profuse diarrhoea to two formed motions a day, no nausea and return of appetite. Parenteral nutrition and Humira were stopped. Duodenal biopsies after 3 months showed complete resolution of villous morphology and were negative for Norovirus on PCR. Stool remained negative for Noroviral RNA. After 6 months Ribavirin therapy was stopped. The patient has remained asymptomatic for the subsequent 9 months with no evidence of recurrent Noroviral excretion. Conclusion: Complete resolution of symptoms and duodenal villous atrophy with clearance of the Norovirus suggests that the association of Norovirus infection with CVID enteropathy is causal. Ribavirin may have activity against Norovirus in vivo and this first ever demonstration of a cure for this condition requires confirmation in other cases. Competing interests: None declared.